Implementation of a data-driven hospitality lexis learning programme - Piyapong Laosrirattanachai,; Sugunya Ruangjaroon, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Data-driven learning has been recognized a potential tool for enhancing learning outcomes. The current study designed a data-driven hospitality lexis learning programme to facilitate the learning of hospitality vocabulary by autonomous learners. To achieve the objectives, the development of learners’ hospitality vocabulary knowledge was measured using the T-test based on pre-testing and post-testing. In addition, the learners’ opinions were explored using two types of questionnaire: the Mentimeter online programme and an open-ended questionnaire. The results of the T-test scores confirmed that the hospitality vocabulary knowledge of learners was improved after learning autonomously using the data-driven hospitality lexis learning programme. The results from the questionnaire indicated that most of the learners thought that the program was convenient, useful, and easily understood. Learners considered that using the programme helped them to be more responsible, to be better at time management, and to expand their vocabulary regarding hospitality. Therefore, using the online programme would be suitable as a recommended alternative to facilitate learning vocabulary for autonomous learners. Thus, such online programmes should be promoted and created in both general and specific fields of learning vocabulary. These findings could be extended to other English-for-specific-purposes contexts to assist learners in dealing with terminology in their fields.